Islamic Law Thinking of Hizbut Tahrir Indonesia - Mulyadi Mulyadi (International Journal of Nusantara Islam, 2019)
This article discusses the thoughts of Islamic law Hizbut Tahrir Indonesia. Using a literature study, this article finds a narrative that Islamic legal thinking Hizbut Tahrir Indonesia refers to an-Nabhani's view which is textual and becomes the domain of debate among scholars. For textualists, Islamic law that must be enforced is of course a fixed duty, through the establishment of the Islamic State. While for some people who understand Islam in contextual terms, Islamic Shari'a or even Islamic Fiqh is not necessarily called sharia. Because the most important thing is the substance of the Shari'a itself.